2009
DOI: 10.1016/j.jcv.2009.06.005
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of multiple test methods for the detection of the novel 2009 influenza A (H1N1) during the New York City outbreak

Abstract: Rapid antigen tests, DFA, R-Mix culture and the xTAG RVP test all detected the novel H1N1 strain, but with highly varied sensitivity. The RVP test provided the best diagnostic option as RVP demonstrated superior sensitivity for the detection of all influenza strains, including the novel H1N1, provided accurate influenza A subtyping and identified a significant number of additional respiratory pathogens.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
284
2
6

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 341 publications
(303 citation statements)
references
References 6 publications
11
284
2
6
Order By: Relevance
“…Rapid antigen tests and direct immunofluorescence assays (DFA) do not distinguish between different influenza A virus subtypes, and therefore cannot confirm an isolate to be pandemic H1N1/ 09. Selected reverse-transcriptase polymerase chain reaction (RT-PCR) systems as well as viral culture together with complementary tests have the ability to subtype influenza A virus strains (50).…”
Section: Laboratory Diagnosismentioning
confidence: 99%
See 1 more Smart Citation
“…Rapid antigen tests and direct immunofluorescence assays (DFA) do not distinguish between different influenza A virus subtypes, and therefore cannot confirm an isolate to be pandemic H1N1/ 09. Selected reverse-transcriptase polymerase chain reaction (RT-PCR) systems as well as viral culture together with complementary tests have the ability to subtype influenza A virus strains (50).…”
Section: Laboratory Diagnosismentioning
confidence: 99%
“…Rapid antigen tests generally have low sensitivity (11%-69%) for detecting pandemic H1N1/09 (50)(51)(52)(53)(54). The sensitivity of all rapid tests decreased markedly with decreasing virus titres in specimens (51).…”
Section: Laboratory Diagnosismentioning
confidence: 99%
“…Previous studies have shown that RIDT sensitivity was correlated with increasing viral titer 2 , 6 , 7 and that higher RIDT sensitivity was found in younger age groups than older groups 3 , 5 , 8 , 9 . However, these studies were conducted either in pediatric patients or with a small sample of older patients.…”
Section: Introductionmentioning
confidence: 99%
“…While these tests were developed and introduced prior to the emergence of influenza A(H1N1) 2009, clinicians have utilized these tests routinely to identify patients infected with influenza A(H1N1) 2009 and to make treatment decisions for those patients. Although the specificity of RIDTs as compared to real‐time RT‐PCR has been shown to be high (90–100%), substantial variation in testing sensitivity (17·8–76·7%) in detecting influenza A(H1N1) 2009 has been reported 1 , 2 , 3 , 4 , 5 …”
Section: Introductionmentioning
confidence: 99%
“…In a large study assessing multiple tests, sensitivities of BinaxNOW® and 3MA + B® as compared to R-Mix culture for the detection of pandemic (H1N1) 2009 virus were 9.6% and 40%, respectively. However, in the latter study, the patient population included adults (mean age 13.7 years, range 2 weeks to 97 years) [7].…”
Section: Performance Of Influenzatop®mentioning
confidence: 99%